Becoming neoliberal policy subjects: Staff members' discursive practices about school climate in Chile - Webb, Andrew; Becerra, Sandra; Sepulveda, Macarena (Critical studies in education, 2023)
Reforms to school climate policies in Chile have led to a marked shift away from punitive approaches for dealing with bullying behaviours, toward more educationally formative processes. Schools in this national context have also been given greater responsibilities for designing anti-bullying practices relevant to their own educational communities. Based on qualitative interviews with staff members in six inner-city schools in the Chilean capital we query whether these policies really enable staff to create positive school climates. We suggest instead that, from a Foucauldian perspective of governance, staff become self-regulated subjects caught between a celebration of administrative autonomy and the pressure to meet national standards of anti-bullying in underfunded and under-resourced schools in socially deprived areas. Rather than solve bullying, staff become more occupied with the doing of new public management. We conclude by suggesting ways in which the current policies could be adapted to better support schools working in these contexts.